COMBINATION OF SGT (SMALL GROUP TEACHING) AND PAL (PEER ASSISTED LEARNING) APPROACH TO FACILITATE LEARNING AMONG MBBS STUDENTS FROM A PRIVATE UNIVERSITY IN MALAYSIA DURING PRE-CLINICAL YEARS - Neena Bhattacharya; Habib, Nasrin; Mamunur Rashid; Sandeep Sugathan; Tahmina Afrose; Ebrahim Nangarath Kottakal (Malaysian Journal of Public Health Medicine, 2020)
Didactic lecture promotes passive learning and fails to motivate students. Small group learning has been widely recommended as it helps to refine understanding of complex issues, to solve the problems, develop critical thinking and apply knowledge to new situations. PALS – a “peer assisted learning” mode where in students discuss in groups and learn from each other. They get motivated and set a platform, which encourages them to communicate and do problem solving. The present study was aimed to evaluate the effectiveness of small group teaching (SGT) and peer assisted learning (PAL) approach among pre clinical medical students. Small groups of students were selected for this study out of the big batch of students pursuing 2nd year MBBS program at AIMST University who were undergoing “respiratory system” block. At the end of lecture-based sessions, a few topics were selected for SGT- PAL session. Students were asked to complete the pretest questions on the selected topics and they were then explained the topics selected for this session. Students had SGT PAL on those selected topics. Then they completed the post test questions on the same topic. Responses obtained for the pre- test and post-test questions were analyzed using SPSS using paired t test and the perceptions on their own understanding using marginal homogeneity test, both showed a significant improvement. SGT and PAL approach helped students to improve understanding of important concepts and can be adopted more widely as an alternative to lectures.